EKSISTENSI PEDAGANG EKONOMI KREATIF WARUNG MOBIL - Popy Popy; Syamsumarlin Syamsumarlin; La Ode Aris (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2019)
This study aims to find out and describe the existence of the creative economy of a food truck and the reproduction of the culture of a food truck business at a merchant shop in BarugaSubdistrict, Kendari City. The theory used is the theory of cultural reproduction and this research is ethnographic research, therefore data collection is carried out by observation techniques involved and in-depth interviews. The data obtained were analyzed descriptively qualitatively. Data analysis is intended to simplify the data obtained so that it is easier to read and understand. The results showed that the existence of a car shop in BarugaSubdistrict was divided into four parts, namely food traders, beverage traders (cold drink), vegetable traders, and fruit traders. In trading using cars, the traders and government individual relations are very closely related, where some government officials take advantage of the existence of this car stall business to make a profit. and the reproduction of the culture of a food truck business can occur because of seeing from the origin area, learning from friends, and seeing sellers who first use food truck.